TINJAUAN ARSITEKTUR TRADISIONAL JAWA DI KOTA LAMA BANYUMAS - Wita & Yohana Widyandini & Nursruwening (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2010)
AbstractIndonesia has so many traditional architecture, that spread throughout the Nusantara, there Minangkabau Architecture, Baduy Architecture, Java Architecture, Kalimantan Architecture, until Asmat Architecture in Papua. Java Architecture as part of the Nusantara Architecture, we must keep and maintain its existence, both in terms of physical buldings and on the philosophy and basic principles of design.Java Architecture here means the architecture that exists around Central Java and Yogyakarta. Java Architecture is divided into several sections based on its territory, namely Pesisir Kilen, Pesisir Wetan, Negariagung, Bagelen, and Banyumasan.District Banyumas, particularly Kota Lama Banyumas, still very fortunate to have quite a lot of architectural heritage, both building architectur of Java, Indische Architecture, and Pecinan Architecture. The buildings are still preserved its authenticity.Considering the variety architectural in Banyumas, particularly in Kota Lama Banyumas, it would be very interesting if that diversity can be explored in more dept, ranging from the history and development, basic concept of design, building form, space plan, and landscape.Keyword : Architecture, Java, Kota Lama Banyumas